ПРОБЛЕМЫ ВНЕШНЕТОРГОВОЙ ДЕЯТЕЛЬНОСТИ КАЗАХСТАНА В УСЛОВИЯХ ВСТУПЛЕНИЯ В ТАМОЖЕННЫЙ СОЮЗ (Journal of Economic Research & Business Administration, 2015)
About world crisis in Kazakh republic and very important things Kazakhtans economical position in world economical crisis, consider about Costumes union outward trade views and primary problems.